ISBAT NIKAH DALAM PERSPEKTIF KOMPILASI HUKUM ISLAM HUBUNGANNYA DENGAN KEWENANGAN PERADILAN AGAMA - Yusna Zaidah (Universitas Islam Negeri Antasari Banjarmasin, 2013)
As one of the executors of judicial power in the courts in the Indonesian Religious Court is given the jurisdiction over civil causes of Islam, one of which is in the field of marriage. As an Islamic court, the substantive law that is used Islamic law, then it is often defined as fiqh, which are certainly vulnerable difference. To bridge differences and to create legal certainty, as well as to realize the Islamic law, then Compilation of Islamic Law (KHI) was born which positively main themes of Islamic law in Indonesia and as one of the law applied in the Religious Court. Especially with regard to matters of marriage is a matter of legalization of marriage in Islamic Law Compilation qualified as a remedy called